Environmental Resources Use and Challenges in Contemporary Southeast Asia Tropical Ecosystems in Transition (Asia in Transition,, 2018)
This edited volume introduces dynamic approaches to the study of Southeast Asia's environmental diversity from different disciplinary perspectives, mainly through a natural and social science interface. It brings together scholars whose research on the region's environmental resource use and shared ecological challenges under the effects of present day globalization, offers insights for possible future directions. The volume introduces unique approaches to the study of Southeast Asia's environmental changes and resource management under the effects of intensifying economic change in the region. It also looks at the slow erosion of Southeast Asia's rich environment and confronts serious issues such as the decrease of biodiversity and tropical forests, and the degradation of peat lands. Concurrently, the volume addresses social issues which are tied to energy-dependent growth and have intensified over the last two decades. It also looks at new roadmaps that are being created to protect, conserve, and manage the environment. By investigating the many ecological issues surrounding us, the volume brings to light the constant struggles we are facing whilst trying to develop a more inclusive and equitable approach to natural resources governance. This volume is relevant for students, academics and researchers who have an interest in the Southeast Asian environment and the way in which we use and interact with it. .